Allyship, Social Justice Values, and Commitment at an Australian Social Service Organization. Issue 47 (2nd November 2021) - Gates, Trevor G.; Achia, Tulsi; Petch, Jemima
Abstract: Social service organizations are increasingly adopting social justice and social inclusion values to inform their public mission statements, service provision, and internal work cultures. Ubiquitous as it is in practice, little is known about how social justice and inclusion orientations may be interpreted and expressed by employees and what implications might present for the management of social service organizations. In a sample of 185 employees of this organization, strong self-reported allyship with four disadvantaged groups was found; Aboriginal and Torres Strait Islander Peoples; sexual and gender diverse people; cultural and linguistically diverse people; and people with disability. A greater alignment between personal and organizational values was associated with greater commitment to the organization's social justice and inclusion mission. Although no direct effect of allyship was observed, values alignment moderated the role of allyship. The impact of allyship on commitment to organizational mission was observed for participants who were high versus low in values alignment. Further implications for management, leadership, and policy within the organization and in the broader Australian social service context are explored.